Analysis of Medication Compliance in Patients with Tuberculosis (TB) - Moh. Subairi; Siti Nur Hasina (Indonesian Journal of Global Health Research, 2026)
Health is a fundamental right of every individual and a crucial measure of a nation's well-being. Infectious diseases such as pulmonary tuberculosis (TB) remain a major public health challenge in Indonesia. TB not only threatens individual health but also has economic and social impacts. It is the third leading cause of death from infectious diseases, ranking third after heart disease and respiratory infections. TB affects all age groups, from children to the elderly. This objective For analyze compliance TB patients in drinking TB medication Method: Design used is analytic with a cross approach sectional. Variable age, type gender, education, occupation, and medication adherence. The population in this study was 31 TB patients in the working area of the Klampis Community Health Center, Bangkalan. Instrument in study use questionnaire level of medication compliance, This questionnaire has been tested for validity and reliability > 0.05. analysis use multiple linear regression. Research result show age almost half of it 56-65 years a total of 14 (45.2%). Education is almost half of them are elementary school student, amounting to 14 (45.2%). Type sex part big man a total of 22 (71%) jobs almost half of it farmer a total of 10 (32.2%) and self-employed a total of 10 (32.2%) and compliance drink partial TB medication big show obedient a total of 21 (67.7%) and no obedient a total of 10 (32.3%) in the working area of the Klampis Health Center, Bangkalan. Pulmonary tuberculosis (TB) is a serious infectious disease and remains a leading cause of death from infectious diseases in Indonesia, especially among vulnerable groups such as children and the elderly. Despite control efforts, long-term treatment and the risk of drug resistance remain major challenges.